UTILIZATION OF MILKFISH (Chanos chanos) BONE POWDER IN MAKING OF RENGGINANG, LOCAL FOOD OF BADUY TRIBE - Fitria Riany Eris; Aris Munandar; Kartina AM; Meutia Meutia; Dian Anggraeni (University of Sultan Ageng Tirtayasa, 2020)
Fishbone have a proportion of 10% of the total weight of fish and usually become fish processing waste that contains nutrients. One fish that has high nutritional value is milkfish. The utilization of milkfish bones can be an alternative way to provide a nutrient-rich food source because it contains a high number of mineral especially Ca and P. In Banten Province, milkfish bone is mainly waste from local food processing of Sate Bandeng (milkfish satay). This paper will discuss the results of research on the utilization of milkfish bone powder in making Rengginang, the local food of Baduy tribe. Baduy rengginang products are added milkfish bone powder with a concentration of 0%, 1%, 2%, and 3%. The products produced were characterized by parameters of linier expansion, crispness, hardness, organoleptic test, Total Plate Count (TPC), and proximate analysis. Rengginang product chosen was the treatment of adding 1% fish bone powder. Rengginang produced has the characteristics of volume expansion, crispness, and hardness in the range of 33.08-47.69%, 104.62-164.67 mm, and 958.20-2600.62 g. Water content, ash content, protein content and the amount of fat in the rengginang produced were 87%, 1.10-3.10%; 8.73-11.20%; and 0.48%. The water and protein content is very important because it is closely related to the physical characteristics of the rengginang produced.